Model permainan lari dan lompat efektif dalam memperbaiki gangguan motorik fisik pada anak dengan keterbelakangan mental - Raharjo, Slamet; Yunus, Mahmud; Subagio, Irmantara; Azidin, Raja Mohammed Firhad Raja (Universitas Nusantara PGRI Kediri, 2024)
This study aims to demonstrate the effect of a running and jumping game model in improving physical motor impairments in children with intellectual disabilities. A pre-experimental design method was used, involving 15 male children aged 11-12 years with intellectual disabilities, who were selected through purposive sampling. The running and jumping game model was conducted for 30 minutes per session, with moderate intensity (60-70% HRmax), three times a week for four weeks. Data collection involved measuring motor skill development, namely running speed and jump height, between pretest and posttest using a 40-meter run test and vertical jump test. Data analysis was conducted using a paired sample t-test with a 5% confidence level. The results showed a significant difference in running speed between pretest and posttest (8.98±0.07 vs. 7.66±0.09 seconds; p=0.001). Similarly, jump height analysis showed a significant difference between the pretest and posttest (21.57±0.98 vs. 31.43±1.72 cm; p=0.001). This proves that the running and jumping game model effectively improves motor skills impairments in children with intellectual disabilities.